Effect of expanded perlite on physical and mechanical properties of cement mortar - Jira Patthanavarit; Mettaya Kitiwan; Nittaya Keawprak; Phacharaphon Tunthawiroon (AIP conference proceedings, 2021)
This study presents an investigation of the physical and mechanical properties of the cement mortar containing expanded perlite as a filler material. The effects of perlite replacement contents and compressive molding force on bulk density, water absorption, and flexural strength were observed. In the mixture of mortar, the content of sand was replaced with perlite ranging from 0 to 15% by weight. The specimen was pressed under the uniaxial force varied from 20 to 40 kN then de-molded and cured in the humidity for 28 days. With the increase in perlite content from 0 to 15 wt%, the bulk density decreased from 2118 kg/m3 to 1586 kg/m3 while the water absorption increased from 7.4% to18.7%. All composites showed a low thermal conductivity in the range of 0.10–0.27 W/m K. The specimen without perlite had a flexural strength in the range of 10.7–14.2 MPa, while that of sample containing perlite was 7.8–12.5 MPa. The cement mortar composite containing 10 wt% expanded perlite and molding at 40 kN showed the highest flexural strength of 12.50±1.36 MPa while the bulk density and water absorption were 1773 kg/m3 and 1.40 %, respectively. The results of this research can be used as a guideline for further development in building materials such as lightweight roof tile, lightweight brick, and ceiling tile.
Keywords: Innovative concrete reinforcement materials; Innovations in Concrete and Construction Materials; Concrete and Cement Materials Research